2017
DOI: 10.17718/tojde.285812
|View full text |Cite
|
Sign up to set email alerts
|

CONNECTIVITY OF LEARNING IN MOOCs: FACILITATORS’ EXPERIENCES IN TEAM TEACHING

Abstract: The role of facilitators in distance learning environments is of substantial importance in supporting the learning process. This article specifically discusses the role of the facilitator in Massive Open Online Courses (MOOC), which are characterized by their stimulation of learning connections. The study analyzes the experiences of 135 facilitators in hybrid courses (cMOOC + xMOOC) where the following are explored: (1) the strategies used by the facilitators to encourage learning connections, (2) the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The facilitators read manuals, watched tutorial videos, and experimented (Doo et al, 2020). Successful facilitators usually took the initiative to collaborate with other facilitators to solve technical problems (Mercado-Varela et al, 2017). These facilitators independently learned about new issues and were willing to take the initiative to facilitate a MOOC much better than others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The facilitators read manuals, watched tutorial videos, and experimented (Doo et al, 2020). Successful facilitators usually took the initiative to collaborate with other facilitators to solve technical problems (Mercado-Varela et al, 2017). These facilitators independently learned about new issues and were willing to take the initiative to facilitate a MOOC much better than others.…”
Section: Discussionmentioning
confidence: 99%
“…Second, besides teaching, facilitators carried the troubling burden of providing essential technical support (Mercado-Varela et al, 2017). Navigating Canvas as a MOOC platform was indeed new for most facilitators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la última década del siglo pasado, la educación ha transitado de un modelo formativo, centrado en objetivos, a otro centrado en competencias y capacidades (Cabero & Llorente, 2015, p. 187), cuyo eje principal es el proceso de formación escolarizado. El aprendizaje involucrado en ello incluye la estructuración de los datos utilizados en diferentes contextos y la búsqueda de conexiones y nuevos significados (León et al, 2014), así como mezclar, restructurar y conectar la información en un grupo de aprendizaje (Cabero & Llorente, 2015, p. 191;Mercado et al, 2017). Y, para continuar aprendiendo, las personas requieren de competencias, esto es, de un saber combinado que conjuga el ser, el hacer y el saber estar en determinadas situaciones, así como la aplicación creativa, flexible y responsable de conocimientos, habilidades y actitudes (Martínez-Palmera et al, 2018), en un ejercicio que les permita reflexionar sobre sí mismos, administrar el tiempo y la información de manera efectiva, colaborar constructivamente con otros y mantener la resiliencia y el control sobre su aprendizaje y sus carreras (European Commission, 2019, p. 11).…”
Section: Antecedentesunclassified
“…Many previous research were conducted where Connectivism is the theoretical framework to support learners' self-directed and collaborative learning. Several studies (Mercado-Varela et al, 2017;Thota, 2015;Titova, 2017) explored ways to engage students in an authentic online collaborative community by incorporating a Massive Open Online Course (MOOC) into a language learning course. The findings revealed that learners were pleased with this intervention because they wanted to share their MOOC experiences with students worldwide, enabling them to be more autonomous whilst achieving their goals online.…”
Section: Connectivism Improves Learners' Motivationmentioning
confidence: 99%